Scoping review protocol of service delivery-related interventions to improve maternal and newborn health in low-income and middle-income countries - Helen Schneider; Solange Mianda; Olamide O Todowede (BMJ Open)
Introduction This review will explore the characteristics of service delivery-related interventions to improve maternal and newborn health in low-income and middle-income countries, comparing three common framing approaches of these interventions (referred to as archetypes), namely, quality improvement (QI), health system strengthening (HSS) and implementation science (IS), over the last 20 years.Methods and analysis This study will review the literature on health service interventions from 2000 to 2020. This will be achieved by searching for English peer-reviewed articles in the following electronic databases EBSCOhost, PubMed, Web of Science, MASCOT/Wotro Map of Maternal Health Research and Google scholar. We will develop a systematic search strategy using a combination of keywords and Boolean operators AND/OR. Eligibility screening and data extraction will be conducted by two independent reviewers, and disagreements resolved by a third independent reviewer. Analyses will be conducted in two steps, a quantitative and a qualitative phase. The quantitative phase will provide a descriptive profile of papers, including the category (QI, HSS, IS, mixed or other) of papers. In the follow-up qualitative phase, all three reviewers will independently code for key concepts in a subset of papers, jointly selected as representing each archetype, and analysed in batches until concept saturation is achieved.Ethics and dissemination This review does not require ethical approval. The results will be published as an article in a peer-reviewed journal and presented to stakeholders involved in implementing health system interventions in maternal and newborn.